Online adaptive geometry predictor of aquaculture fish-nets - Potyagaylo, Svetlana; Loizou, Savvas (My University, 2014)
This paper proposes an online adaptive geometry predictor for aquaculture fish-nets. The 3D fish-net model is based on a lumped-mass method according to which the net meshes are represented by four interconnected cylindrical elements. The external forces are applied at the center of each element, while the internal forces are calculated as tension forces between two neighboring mass points. The model is validated through several simulations for a small-scale open cylinder exposed to steady uniform current. The preliminary simulation results of the full aquaculture net system are provided as well. The proposed predictor will be used as an information source in the control architecture of an underwater vehicle.
Keywords: Remotely operated vehicles; Autonomous system; Visual inspection; Fish farm nets; Underwater vehicles